THE EFFECT OF PERCEIVED USEFULNESS, PERCEIVED ENJOYMENT, BRAND TRUST FROM VIDEO REELS AS A SOCIAL MEDIA MARKETING STRATEGY ON CUSTOMER LOYALTY OF RETAIL STORE IN SUMMARECON MALL KELAPA GADING - Jeaniefer Jeaniefer; Agung Stefanus Kembau (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Amid rapid digitalization, social media has become a key platform where brands compete for consumer attention. This study explores how Instagram Reels affect customer loyalty by enhancing perceived usefulness, enjoyment, and brand trust in Summarecon Mall Kelapa Gading retail stores. Using a quantitative approach with purposive sampling, data was gathered from 111 respondents via surveys and analyzed using SmartPLS 4.1.0.9. The results indicate that social media marketing has a positive effect on perceived usefulness and enjoyment, whereas its influence on brand trust is negligible. Perceived usefulness strongly influences both brand trust and enjoyment. The study highlights Instagram Reels as an effective tool for boosting customer loyalty and offers insights for retail businesses and mall management. However, the sample primarily consists of young, active Instagram users, potentially underrepresenting the broader market. Ultimately, effective content is not just visually appealing but also builds meaningful customer connections. Keywords: Social Media Marketing; Perceived Usefulness; Perceived Enjoyment; Brand Trust; Customer Loyalty